2015
DOI: 10.1186/s12974-015-0440-3
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin drives alternative macrophage activation and improves recovery and tissue sparing in contusion spinal cord injury

Abstract: BackgroundMacrophages persist indefinitely at sites of spinal cord injury (SCI) and contribute to both pathological and reparative processes. While the alternative, anti-inflammatory (M2) phenotype is believed to promote cell protection, regeneration, and plasticity, pro-inflammatory (M1) macrophages persist after SCI and contribute to protracted cell and tissue loss. Thus, identifying non-invasive, clinically viable, pharmacological therapies for altering macrophage phenotype is a challenging, yet promising, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 62 publications
10
108
0
Order By: Relevance
“…Specifically, AZM doses ranging from 10–160 mg/kg decreased M1 gene expression in macrophages while both the lowest (10 mg/kg) and highest (160 mg/kg) doses administered increased M2 macrophage gene expression. Previously, we observed that this AZM-mediated shift in polarization following a pretreatment paradigm is associated with improved tissue sparing and functional recovery14. Therefore, these findings highlight the potential for AZM to serve as an effective treatment for SCI.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Specifically, AZM doses ranging from 10–160 mg/kg decreased M1 gene expression in macrophages while both the lowest (10 mg/kg) and highest (160 mg/kg) doses administered increased M2 macrophage gene expression. Previously, we observed that this AZM-mediated shift in polarization following a pretreatment paradigm is associated with improved tissue sparing and functional recovery14. Therefore, these findings highlight the potential for AZM to serve as an effective treatment for SCI.…”
Section: Discussionsupporting
confidence: 53%
“…Previously we observed that AZM treatment, begun prior to SCI, alters macrophage activation and improves tissue repair and functional recovery14. The purpose of this study was to determine if AZM treatment, initiated after SCI, alters the macrophage response to injury.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The lesion epicenter for each animals was identified as the tissue section with the least amount of axon and myelin staining on cross-sections double-stained with Eriochrome cyanine/neurofilament (EC/NF) as described previously (Zhang et al, 2015a; 2015b). …”
Section: Methodsmentioning
confidence: 99%
“…We found that knockdown of RyR2 significantly promoted the recovery of structural and functional injury in spinal cord, as evidenced by reduction of lesion volume and increase of BBB and CBS scores. Inflammation plays an important role in the injury of spinal cord after trauma and reduction of inflammation was considered to be an important intervention for SCI therapy [23,24]. Since downregulation of RyR2 prohibited the increase of proinflammatory cytokines IL-1β and TNFα, it was indicated that RyR2 was involved in the development of inflammation, which contributed to traumatic injury of spinal cord.…”
Section: Discussionmentioning
confidence: 99%